STANDARDISASI PARAMETER SPESIFIK DAN NON SPESIFIK EKSTRAK ETANOL BUAH ASAM GELUGUR (Garcinia atroviridis Griff.) - Galih Samodra (Viva Medika, 2019)
Acid gelugur fruit (Garcinia atroviridis) is one of the Garcinia families that has long been used as traditional medicine. Gelugur acid has been widely used as a cooking spice by Malay people, but it also has the ability to reduce cholesterol. Besides that, it has antioxidant properties and can reduce body weight and cholesterol. The purpose of this study was to establish specific parameter standards and non-specific parameters from the ethanol extract of acid gelugur fruit. The extract was obtained by maceration method using 70% ethanol with a rendament of 37.15%. Specific parameters include observations of organoleptic extracts of tamarind fruit showed, dark brown, distinctive smelling, and sour. Contains several sekendur metabolites such as flavonoids and saponins. The level of the compound that is soluble in water is 3.6%, while the content of the compound dissolved in ethanol is 3.9%. Total ash content of 2.99%. Non-specific parameters include acid insoluble ash content of 1.03%. The drying rate of geluguric acid simplicia was 7.20%. Water content of sour fruit gelugur extract was 13%.